Related-party transactions: evidence of audit fees in publicly companies in the brazilian market - Santo Lima, Ana Claudia; Silva do Carmo, Carlos Henrique; Alves Gonçalves Magalhães , Ketlyn (Advances in Scientific and Applied Accounting, 2023)
Purpose: The study aimed to identify the influence of related party transactions (RPTs) on audit fees (HonAud) of publicly traded companies in the Brazilian market. Method: AudFee was applied as a dependent variable. As for transactions with related parties, an independent variable, it was decided to use the RPTs in their logarithmic form (Habib et al., 2015; Pratama, 2018; Ali et al., 2021). The collection of economic and financial data was carried out at Economática database and the audit information was taken from the Reference Form, finally, the data referring to the RPTs were collected from the individual statements of the companies in the sample. Results or Discussion: The results suggest that the RPTs of sales, purchases and totals contribute to the increase of the audit risk, being possibly more complex to be verified than transactions with third parties. And, therefore, they are associated with higher amounts of audit fees charged when providing external audit services. Contributions: The research contributes to the literature by suggesting that sales and purchasing RPTs act as determinants for the increase in audit fees. It has implications for auditors, as RPTs constitute potential audit risks and require a more specific investigation during the assurance work. Finally, the findings provide guidance for regulators to establish standards for the disclosure of RPTs, as this type of operation can be used to obscure accounting information.